2022
DOI: 10.3390/nano12213768
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Performance of UV Photodetector of ZnO Nanorods Decorated with Al Nanoparticles

Abstract: In this work, localized surface plasmon resonance (LSPR) mediated by aluminum nanoparticles (Al NPs) was investigated to enhance the ultraviolet (UV) response of the zinc oxide nanorods (ZnO NRs) grown by the hydrothermal method. The ZnO NRs were characterized by scanning electron microscope, energy dispersive spectroscopy, X-ray diffractometer, Raman spectrometer, ultraviolet-visible spectrophotometer and fluorescence spectrometer. The results show that the morphology and crystalline structure of the ZnO NRs … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…Plasmonic nanoparticles such as Al also tend to increase the sensitivity of the ZnO nanorod photodetector. For example, compared to bare ZnO nanorods, devices with plasmonic Al nanoparticles show increase in their responsivity from 53 to 267 mA W −1 and in their sensitivity from 9.5 to 47.8 under 325 nm UV light (5 mW cm −2 ) at 3.0 V bias [63]. In addition, Liu et al demonstrated that photoresponse of ZnO nanorods can be enhanced by covering it with a polymer such as PMMA.…”
Section: Electrical and Optoelectrical Properties Of Zno Nanorodsmentioning
confidence: 99%
“…Plasmonic nanoparticles such as Al also tend to increase the sensitivity of the ZnO nanorod photodetector. For example, compared to bare ZnO nanorods, devices with plasmonic Al nanoparticles show increase in their responsivity from 53 to 267 mA W −1 and in their sensitivity from 9.5 to 47.8 under 325 nm UV light (5 mW cm −2 ) at 3.0 V bias [63]. In addition, Liu et al demonstrated that photoresponse of ZnO nanorods can be enhanced by covering it with a polymer such as PMMA.…”
Section: Electrical and Optoelectrical Properties Of Zno Nanorodsmentioning
confidence: 99%
“…The last decade has witnessed the rapid progress of optoelectronic devices owing to their crucial impact on several industries, such as light images in cameras, controlling the intensity of street lighting, spaceships, military laser equipment, and highly technology controlled windows, imaging, UV radiation monitoring, and wearable devices [ 1 , 2 , 3 , 4 , 5 , 6 , 7 ]. Among these devices, photodetectors must be suitable for various fields.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, photodetectors display outstanding detection ability covering a broad spectral range. Such a device is highly dependent on the activated photons reaching its surface, which will produce free electrons able to polarize the surface and induce a current density (J ph ) [ 4 , 5 ]. For the majority of recent semiconductors, this is directly proportional to light intensity, where the elevation of the photon flux liberates more electrons on the surface.…”
Section: Introductionmentioning
confidence: 99%
“…ZnO has been utilized extensively as a wide-band-gap semiconductor. It is also a versatile material with a wide range of different shapes as well as morphologies, such as nanosprings, nanocombs, nanobelts, nanocages, and nanowires [ 18 , 19 , 20 , 21 , 22 ]. Compared to other noble metals (Au/Pt), silver (Ag) nanoparticles exhibit unique characteristics, including biocompatibility, excellent catalytic activity, low toxicity, antibacterial qualities, and affordability, and, hence, they were chosen in our study to decorate ZnO NRs [ 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%